Answer:
-2
<em>BRAINLIEST, PLEASE!</em>
Step-by-step explanation:
5 - 3(2a + 1) = -4a + 10
5 - 6a - 3 = -4a + 10
2 - 6a = -4a + 10
-2a = 8
a = -4
-4 + 2 = -2
9514 1404 393
Answer:
700
Step-by-step explanation:
You figure this out by multiplying 70 by 10:
10×70 = 700
Answer:
Hot Dog and Bologna
Step-by-step explanation:
ANSWER
![y= -3{(x + 4)}^{2} + 2](https://tex.z-dn.net/?f=y%3D%20-3%7B%28x%20%2B%204%29%7D%5E%7B2%7D%20%20%2B%202)
EXPLANATION
The given function is:
![y= -3x^2-24x-46](https://tex.z-dn.net/?f=y%3D%20-3x%5E2-24x-46)
Factor -3 for the first 2 terms.
![y= -3(x^2 + 8x)-46](https://tex.z-dn.net/?f=y%3D%20-3%28x%5E2%20%2B%208x%29-46)
We add and subtract the square of the coefficient of x.
![y= -3(x^2 + 8x + {(4)}^{2} ) - - 3( {4)}^{2} -46](https://tex.z-dn.net/?f=y%3D%20-3%28x%5E2%20%2B%208x%20%2B%20%20%7B%284%29%7D%5E%7B2%7D%20%29%20%20-%20-%203%28%20%7B4%29%7D%5E%7B2%7D%20-46)
Factor the perfect square trinomial.
![y= -3 {(x + 4)}^{2} ) + 48 -46](https://tex.z-dn.net/?f=y%3D%20-3%20%7B%28x%20%2B%204%29%7D%5E%7B2%7D%20%29%20%20%2B%2048%20-46)
The vertex form is:
![y= -3{(x + 4)}^{2} + 2](https://tex.z-dn.net/?f=y%3D%20-3%7B%28x%20%2B%204%29%7D%5E%7B2%7D%20%20%2B%202)